(untitled) (Annals of Medical Research, 2023)
Aim: Primary central nervous system lymphoma (PCNSL) is an important topic in hematology due to its rare, aggressive course, difficult diagnosis and special treatment requirements. This bibliometric analysis study aimed to examine PCNSL-related publications published since the last 2000 and to identify potential points of future research. Materials and Methods: Web of Science Core Collection documents published between 2000 and 2022 were analyzed using selected keywords. The obtained data were visualized with bibliometric tools. Publishing countries, organizations, journals, authors, references, and keywords were all examined comprehensively. Results: 1,160 articles on PCNSL published since 2000 were retrieved. These publications tend to focus on research in oncology (n=456, 39.310%), clinical neurology (n=354, 30.517%), and hematology (n=173, 14.914%). Search criteria revealed that 6,458 authors from 65 different countries and 1,570 organizations worldwide contributed to PCNSL articles. Conclusion: Studying research on PCNSL is crucial to improve our knowledge of this disease and to create new treatment strategies. It is very important to keep in mind that the characteristics and trends in PCNSL research may change over time as new findings and developments in the field are discovered. The results of this study may provide guidance for researchers working in this area.